Recent excavations in Peeblesshire - MacLaren, Alastair; Lisowski, F P; Spence, T F (Proceedings of the Society of Antiquaries of Scotland, 1968)
NR 085234; 098396. At Weird Law a low bank surrounded a circular level space (34ft diameter) with a central low turf-covered mound (14ft diameter). Excavation revealed the sequence: ring of stones enclosing two central pits, which were then refilled and a cremation pyre was built and fired; four pits, dug through the ashes to receive the bones of two bodies, were then refilled and sealed with stones. Previously thought to be hut circles, such sites are largely confined to the Highland Zone but can be compared with, eg, henges. A 14C date of 1490 + 90 BC agrees well enough with that from the comparable site at Whitestanes Moor. Broughton Knowe, a low turf-covered mound, had been plundered; a small quantity of cremated bone and charcoal, flint scrapers and sherds indicated the original burial, laid on the old ground surface. The surrounding ditch, refilled soon after being dug, contained packing stones disposed as if to support a tent-like covering for the central area. An EIA date is not excluded but the Bronze Age seems more likely.